Comparison of Frontozygomatic versus Sigmoid Notch Approach for Extraoral Maxillary Nerve Block Anesthesia: A Prospective Clinical Trial - Radder, Kiran (J Maxillofac Oral Surg, 2017)
BACKGROUND: With definitive indications, extraoral techniques of achieving regional nerve blocks are a boon to oral and maxillofacial surgical practice. Though less commonly practiced, since general anesthesia is more favored, certain medical conditions favor the use of regional nerve blocks over general anesthesia. To block the maxillary nerve extraorally, sigmoid notch approach and frontozygomatic approach have been previously described in the literature, but a clinical trial comparing these techniques is sparse. This study attempts to compare both the approaches for their efficacies while paying an equal attention to the associated complications. MATERIALS AND METHODS: Two hundred patients aged between 40–90 years of ASA 1 and 2 category were equally divided into two groups and underwent extraction of maxillary teeth under local anesthesia using 2% lignocaine with 1:80,000 adrenaline. Frontozygomatic approach to reach the foramen rotundum was employed in group A (n = 100) and sigmoid notch approach in group B (n = 100). Pain during injection, time required for onset of subjective and objective symptoms of anesthesia and duration of anesthesia were the study parameters. Associated complications were documented and discussed. Student’s unpaired t test was used for statistical evaluation. RESULTS: Although both the techniques were found to be feasible, statistical evaluations favored the frontozygomatic approach with respect to faster onset and a longer duration of the anesthetic effect. The anatomical considerations in either techniques suggested that the incidence of potential complications of accidental entry of the needle into the orbit, skull and vessel injuries was higher when using sigmoid notch approach as against the frontozygomatic approach. CONCLUSION: Though sigmoid notch approach, described widely in the literature, can be employed successfully, certain anatomical considerations and technical modifications in the frontozygomatic approach have made the latter a more practical and feasible approach. When both the maxillary and the mandibular nerves need to be blocked simultaneously, sigmoid notch may be employed, but isolated maxillary nerve block is better achieved using frontozygomatic approach.